2021
DOI: 10.3389/fonc.2020.611617
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model for Optimal Primary Debulking Surgery Based on Preoperative Computed Tomography Scans and Clinical Factors in Patients With Advanced Ovarian Cancer: A Multicenter Retrospective Cohort Study

Abstract: ObjectiveThis study assessed the predictive value of preoperative computed tomography (CT) scans and clinical factors for optimal debulking surgery (ODS) in patients with advanced ovarian cancer (AOC).MethodsPatients with AOC in International Federation of Gynecology and Obstetrics (FIGO) stage III-IV who underwent primary debulking surgery (PDS) between 2016 and 2019 from nine tertiary Chinese hospitals were included. Large-volume ascites, diffuse peritoneal thickening, omental cake, retroperitoneal lymph nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…We found that age did not significantly differ among two groups of debulking surgery, similar to prior study [57]. In contrast, a multivariate analysis from Gu et al [58] found age >60 years become a significant predictor for suboptimal debulking surgery with OR 2.39 possibly due to younger cut-off of elderly we used in this study. Other variables such as obesity were not significant predictors of suboptimal debulking surgery in contrast with Suknikhom et al [17].…”
Section: Suboptimal Debulking Surgery Predictorssupporting
confidence: 86%
“…We found that age did not significantly differ among two groups of debulking surgery, similar to prior study [57]. In contrast, a multivariate analysis from Gu et al [58] found age >60 years become a significant predictor for suboptimal debulking surgery with OR 2.39 possibly due to younger cut-off of elderly we used in this study. Other variables such as obesity were not significant predictors of suboptimal debulking surgery in contrast with Suknikhom et al [17].…”
Section: Suboptimal Debulking Surgery Predictorssupporting
confidence: 86%
“…The other one patient was at advanced age and had a poor performance status that could not tolerate primary cytoreduction. After receiving NACT, the tumor burden of all three patients were significantly reduced by CA125 and CT scans ( 22 , 23 ). Among all 22 patients, 90.9% of patients underwent standard ovarian surgery, including cytoreductive surgery (63.6%), ovarian cancer staging surgery (18.2%), and fertility preservation staging surgery (9.1%).…”
Section: Resultsmentioning
confidence: 96%
“…In this study, we assessed the preoperative objective, simple, and easily identifiable predictors of SDS and developed a risk prediction model. The AUCs of our model (training set = 0.951, internal validation set = 0.868, external validation set = 0.773) were higher than those of other models [12,14,18] (Fig. 4).…”
Section: Discussionmentioning
confidence: 71%
“…In models predicting SDS, most studies have included CA-125 as one of the variables. The cutoff value of CA-125 was 500 U/mL by Suidan [ 11 ], 800 U/mL by Yu Gu [ 14 ], and 420 U/mL by Maliheh [ 17 ]. However, the cutoff value of the present study was 1484 U/mL, which is significantly higher than those of the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation